Kontribusi Lingkungan Belajar Dan Motivasi Belajar Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Takdir, Takdir; Sudiyono, Sudiyono; Putra, Dwi Fauzia (Efektor, 2023)
The research was conducted using a survey method with a questionnaire as the instrument. The subjects of the study were 286 students in the upper classes of SDN Gugus 1 Bungku Barat Morowali. Data analysis was performed using multiple regression analysis, the F-test, and the t-test. The results of the regression analysis showed a calculated F-value of 2609.473 with a significance level (p) of 0.000. The p-value of 0.000 < 0.05, and the coefficient of determination (R-square) was 0.949, indicating that the learning environment and learning motivation of students jointly contributed to 94.9% of the students' learning outcomes in Social Studies (IPS). The remaining 5.1% was attributed to other variables outside of this regression equation. Simultaneously, there is a significant contribution of the learning environment and learning motivation to the students' IPS learning outcomes in elementary school. Partially, there is a significant contribution of the learning environment to the students' IPS learning outcomes in elementary school. Partially, there is a significant contribution of learning motivation to the students' IPS learning outcomes in elementary school. It is expected that schools and parents should collaborate intensively to support the availability of a conducive learning environment for students, both at school and at home. The role of teachers as motivators should be optimized in encouraging students' learning motivation